Solubility, viscosity and rheological properties of water-soluble chitosan derivatives - Siriwat Tungtong (2018)
An investigation and comparison of solubility, viscosity and rheological properties under neutral, acidic and alkaline conditions of water-soluble chitosan derivatives, viz. O-carboxymethyl chitosan, N,O-carboxymethyl chitosan, N-[(2-hydroxy-3-trimethylammonium)propyl] chitosan chloride and O-carboxymethyl-N-[(2-hydroxy-3-trimethylammonium)propyl] chitosan chloride, was undertaken. © 2012 by Maejo University, San Sai, Chiang Mai, 50290 Thailand.